Characterization and necrosis-inducing activity of necrosis- and ethylene-inducing peptide 1-like proteins from Colletotrichum australisinense, the causative agent of rubber tree anthracnose - Liu, Xianbao; Li, BoXun; Cai, Jimiao; Yang, Yang; Feng, Yanli; Huang, Guixiu (Frontiers in Microbiology, 2022)
Colletotrichum australisinense, a member of the Colletotrichum acutatum species complex, is an important pathogen causing rubber tree anthracnose. Genome-wide comparative analysis showed this species complex contains more genes encoding necrosis- and ethylene-inducing peptide 1-like proteins (NLPs) than other Colletotrichum species complexes, but little is known about their roles in pathogenesis. The aim of this study was to analyze C. australisinense NLPs and characterize their putative role as virulence factors associated with rubber tree anthracnose. According to phylogenetic relationship, conserved the cysteine residues and the heptapeptide motif (GHRHDWE), eleven NLPs were identified and classified into three types. Five of the 11 NLPs were evaluated for necrosis-inducing activity. CaNLP4 (type 1) could not induce necrosis in host or non-host plants. By contrast, both CaNLP5 and CaNLP9 (type 1) induced necrosis in host and non-host plants, and necrosis-inducing activity was strongest for CaNLP9. CaNLP10 (type 2) and CaNLP11 (type 3) induced necrosis in host but not non-host plants. Substitution of key amino acid residues essential for necrosis induction activity led to loss of CaNLP4 activity. Structural characterization of CaNLP5 and CaNLP9 may explain differences in necrosis-inducing activity. We evaluated the expression of genes coding CaNLP by reverse transcription polymerase chain reaction (RT-PCR) and quantitative real-time PCR (qRT-PCR) at different time-points after pathogen infection. It was found that genes encoding CaNLPs with different activities exhibited significantly different expression patterns. The results demonstrate that CaNLPs are functionally and spatially distinct, and may play different but important roles in C. australisinense pathogenesis.